PERILAKU PENYIMPANGAN SEKSUAL DALAM PERKAWINAN PERSPEKTIF HUKUM ISLAM - Hidayat, Herdi; Asni; Hilal, Fatmawati (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
Abstract This research discusses sexual deviant behavior in the form of coercion in sexual relations (Marital Rape) and Sadomasochism. The author tries to examine cases of sexual deviant behavior in marriage that focus on Islamic Law. The main problem in this study is how the Islamic Law perspective on the imposition of sexual relations (Marital Rape) in marriage, how the Perspective of Islamic Law Sadomasochism, and how to overcome sexual deviance in marriage. The type of research used is library research by referring to the results of previous research, such as books, journals and articles that can be accessed online. The results showed that, the behavior of sexual deviance in marriage according to the perceptive islamic law is the coercion of sexual relations between husband and wife (Marital Rape) if the wife is sick or is in her menstrual period. However, if the wife is not in a state of illness and then forced to have sexual intercourse because the wife refuses to do so then it is not included in Marital Rape. the behavior of sadism and masochism (Sadomasochism) in conjugal relationships is makruh. Because it contains elements of persecution and danger. It is in an effort to achieve mutual sexual satisfaction, which will give happiness and harmony in the household. The implications of this study are the implementation of premarital courses (suscatin), reporting to KPAI, KOMNAS HAM, as well as supervising and learning adolescents in order to avoid sexual deviance and not hesitate to report if there are sexual deviance. Keywords: Sexcual deviant, Marital Rape, Sadomasochism.